Usulan Strategi Pemasaran Toko Retail RC Motogarage - Penyedia Helm Sepeda Motor dan Peralatan Keselamatan Premium - Frans Frans; Reyner Alexander (Bina Ekonomi, 2017)
Along with Indonesia's economic growth and the need for practical and economical transportation vehicle, the number of two-wheeled motor vehicles or motorcycles users is increasing. This also resulted in an increasing demand for motorcycle safety gear given the importance factor of safety for motorcycle users. RC Motogarage, a retail store that sells motorcycle safety gear in Bandung, chooses to sell premium safety equipment products because the level of safety provided by the premium brand is relatively better than local brands. Being the current market leader, RC Motogarage sales decreased significantly due to the emergence of competitors. By using cluster analysis and factor analysis research methods, this research aims to produce the best solution to improve the marketing strategies of RC Motogarage. Key words : Retail, marketing strategy